Blood Cells Morphometry and Descriptive Morphology of Captive Changeable Hawk Eagles (Nisaetus chirratus) at Wildlife Rescue Centre Jogja - Hardian, Andreas Bandang; Nugrahani, Warih Pulung; Rahmawati, Irhamna Putri; Megarani, Dorothea Vera (Acta VETERINARIA Indonesiana, 2023)
Providing qualitative and quantitative haematologic references of neglected captive wild animals is pivotal for the sanctuary health management and improvement. Changeable hawk eagles (Nisaetus chirratus) are abundantly kept in sanctuary in which no haematologic reference is ever reported. This study aimed to present the visual keys and morphometric references of changeable hawk eagles’ blood cells as the standard for further haematologic count. The peripheral blood smears were prepared and collected from eight changeable hawk eagles kept at Wildlife Rescue Centre Jogja then stained with 10-fold diluted Giemsa stain following the standard manners. All slides were inspected and captured under camera-equipped microscope which then were morphologically and morphometrically evaluated using ImageJ version 1.52a. As the changeable hawk eagles are naturally present in dark and bright morph, we statistically compared the blood cells morphometric parameters between morph-based groups. Changeable hawk eagles’ erythrocytes were oval shaped with occasional morphologic variation. Leukocyte consisted of polymorphonucleated granulocytes - with exception of basophils which lacked nuclear lobulation - and mononucleated agranulocytes. There were significant differences (P<0.05) of all erythrocyte morphometric parameters, heterophils diameter, and lymphocytes diameter between dark and bright morph group. Overall, the morphologic properties of changeable hawk eagles’ blood cells were visually identical to other avian species though the blood cells morphometry might be comparatively different.